Digital Reporting as Mediator of Leadership, Partnership, and Performance Effectiveness in Palembang Narcotics Prevention - Mario Ivanry; Sari Sakarina; Yolanda Veybitha (UTSAHA: Journal of Entrepreneurship, 2026)
Narcotics distribution in Palembang City continues to represent a serious problem, with more than 1,600 cases per year recorded at Polrestabes Palembang. Conventional prevention models have begun to demonstrate their limitations, particularly in terms of policy fragmentation and the limited utilization of digital technology as a reporting instrument. This study aims to analyze the influence of Leadership and Partnership on Personnel Performance Effectiveness in the prevention of narcotics distribution in Palembang City, with Digital-Based Reporting as a mediating variable. A quantitative research method was employed using a saturated sampling technique involving 70 personnel as respondents. Data were tested using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results reveal that Leadership and Partnership have a significant influence on Digital-Based Reporting, which in turn has a positive impact on Personnel Performance Effectiveness, with Partnership identified as the most dominant variable (β = 0.642). These findings confirm that Digital-Based Reporting serves as a crucial mediator in improving the quality of personnel performance. Statistically, the R-Square values indicate that the Leadership and Partnership variables contribute 96.0% to the effectiveness of Digital-Based Reporting. Furthermore, the model is capable of explaining 98.8% of the variance in Personnel Performance Effectiveness. These findings affirm that the synergy of visionary leadership and solid partnership, integrated through Digital-Based Reporting, constitutes a key factor in optimizing personnel performance in narcotics prevention.